G439 Recognising and reporting child abuse in clinical practice: a qualitative study of paediatricians in bogotá, colombia. (25th October 2020) - Whiteside, C; Feron, F; Pinzon, A
Abstract : Aims: Child abuse is extremely prevalent worldwide but overwhelmingly underreported and underrecognised, meaning the scope of the problem is often underrepresented. Paediatricians are in a unique position to identify and stop cases of child abuse from escalating. This purpose of this study was to identify potential barriers amongst paediatricians in recognising and reporting child abuse cases in their practice. UNICEF highlighted that in Colombia, careful attention was required to tackle violence against children, as some people considered exploitation and abuse as normal or acceptable and that there is an 'insufficient budget, services and trained human resources..to meet the needs of children'. Methods: A review of relevant literature highlighted under recognition and underreporting of suspicious cases of abuse and described confusion and inconsistencies in paediatrician's role and involvement in detection and reporting. This descriptive phenomenological study utilised a qualitative research design with 9 in-depth semi-structured interviews, conducted with paediatricians working in clinical practice in Bogotá, Colombia. Results: The main barriers noted were fear, inadequate training and guidelines and lack of confidence or understanding in the follow up process. Factors which were shown to positively impact on reporting included the role of the multidisciplinary team, level of perceived responsibility, and their relationship and level of communication with the patient and their family. These factors were all shown to impact on a paediatricians clinical reasoning in determining if a child is being abused and if they should report it, along with their gut feeling and ability to identify signs of abuse. Conclusion: Child abuse is a complex interplay of factors, with a large difficulty in clinical practice in identifying the 'cut off' between 'normal parenting' and abuse. This study highlighted the need for standardisation and renewal of training on child abuse for paediatricians throughout their undergraduate and postgraduate career, with screening tools and guidelines that would increase paediatricians' awareness and confidence in dealing with child abuse. The results of the study highlight a framework with a complex interlinking and interdependency of factors affecting clinical practice with no 'one size fits all approach' in regard to recognising, reporting and safeguarding an at-risk child.